2017
DOI: 10.18632/oncotarget.23044
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the metabolism by trimetazidine enhances myoblast differentiation and promotes myogenesis in cachectic tumor-bearing c26 mice

Abstract: Trimetazidine (TMZ) is a metabolic reprogramming agent able to partially inhibit mitochondrial free fatty acid β-oxidation while enhancing glucose oxidation. Here we have found that the metabolic shift driven by TMZ enhances the myogenic potential of skeletal muscle progenitor cells leading to MyoD, Myogenin, Desmin and the slow isoforms of troponin C and I over-expression. Moreover, similarly to exercise, TMZ stimulates the phosphorylation of the AMP-activated protein kinase (AMPK) and up-regulates the peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 74 publications
3
28
0
1
Order By: Relevance
“…Therefore, the MFimmunometabolic approach, which does not merely reduce inflammation but also increases M2 activation, might potentially promote muscle regeneration, limiting muscle loss in cachexia. In this regard, we have recently found that the metabolic modulator trimetazidine (TMZ) enhances myogenesis in cancer cachexia in mice (101), along with stimulating M2 reprogramming in vitro (unpublished observations).…”
Section: E Cachexiamentioning
confidence: 95%
“…Therefore, the MFimmunometabolic approach, which does not merely reduce inflammation but also increases M2 activation, might potentially promote muscle regeneration, limiting muscle loss in cachexia. In this regard, we have recently found that the metabolic modulator trimetazidine (TMZ) enhances myogenesis in cancer cachexia in mice (101), along with stimulating M2 reprogramming in vitro (unpublished observations).…”
Section: E Cachexiamentioning
confidence: 95%
“…Exercise is also able to activate myogenesis, impinging on satellite cells (SCs) proliferation and differentiation [70] . Accordingly, TMZ treatment modulates the behavior of differentiating murine myoblast, increasing fusion capacity, markers of myogenesis and MyHC levels [71] . These effects are associated with increased expression of metabolic regulators such as PGC-1α and activated AMPK, suggesting an increase in oxidative metabolism [71] .…”
Section: Targeting Exercise-induced Pathways and Muscle Metabolism Asmentioning
confidence: 99%
“…Accordingly, TMZ treatment modulates the behavior of differentiating murine myoblast, increasing fusion capacity, markers of myogenesis and MyHC levels [71] . These effects are associated with increased expression of metabolic regulators such as PGC-1α and activated AMPK, suggesting an increase in oxidative metabolism [71] . Similar results have been obtained in isolated murine SCs, in which TMZ increases some markers of differentiation as compared to control [71] .…”
Section: Targeting Exercise-induced Pathways and Muscle Metabolism Asmentioning
confidence: 99%
See 2 more Smart Citations